(untitled) (Minerva, 2019)
Apollo’s oracle is mentioned three times in this Sophoclean play and, in spite of this, the goods never seem so far away from human initiatives. Orestes consultation with the oracle suggests that his decision was already taken and his report of Apollo’s answer leaves ambiguous who understands the revenge as a “just sacrifice”. Orestes’ motivations are clearly political and patrimonial. Sophocles exploits such ambiguity to underline the diversity of perspectives of brother and sister (the bipartite prologue suggests it). Fixated on her brother Electra, spent by her suffering, doesn’t find a proportional affection and attention from him, a revenger who comes back to take possession of his inheritance. As Apollo had previewed, the revenge will succeed by deceit and dissimulation, deprived of warrior’ arete. Will Orestes be sure, after his revenge, that the good is with him? Even there Sophocles keeps an ambiguous formulation. The price of the liberation of this house is too high. The play ends in an unglorious and depressing atmosphere.